The Balkan contact zone at the turn of the century - Garabedjan, Agop (Balcanica Posnaniensia. Acta et studia, 2009)
The article addresses the issue of the Balkans as a special contact zone where different civilisations, religions and cultures have clashed for centuries. The background to the study is an analysis of the historical and geopolitical conditions of the region, starting with the division of the Roman Empire in the 4th century, through the period of Byzantine domination, the expansion of Islam and Ottoman rule, to the nationalist processes of the 19th and 20th centuries and the political transformation after the collapse of Yugoslavia and the Soviet Union. The aim is to show the mechanisms of shaping national and state identities in the context of overlapping religious, ethnic and cultural differences. The author asks how the coexistence and conflict of these factors influenced the dynamics of the formation and disintegration of state structures and the political stability of the region. The analysis uses a historical and political science approach based on historical sources and the literature on the subject. The conclusions indicate that the Balkan contact zone is an area of high identity and political dynamics. The author emphasises that freezing ethnic and religious conflicts is a short-term and potentially dangerous solution, and that only political compromises based on the recognition of the cultural and ethnic diversity of the Balkans will ensure lasting stability.